2016
DOI: 10.1186/s12891-016-1311-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain in patients with rotator cuff tears

Abstract: BackgroundRecent studies have confirmed the existence of neuropathic pain (NeP) components in patients with musculoskeletal disorders. However, the presence of NeP in patients with rotator cuff tears has not been investigated thus far. Therefore, we studied the prevalence of NeP and the prognostic factors for NeP in patients with rotator cuff tears.MethodsData were collected from 110 patients with rotator cuff tears, diagnosed by physical examination and magnetic resonance imaging, who attended an outpatient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…4 In patients with rotator cuff tears, the prevalence of neuropathic pain has been found to be as high as 15.8%. 15,17,18 The DN4 score is a reliable, validated, quick, and sensitive tool for evaluating neuropathic pain. 37 However, the effect of neuropathic pain on acute pain and analgesic use after surgery has never before been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…4 In patients with rotator cuff tears, the prevalence of neuropathic pain has been found to be as high as 15.8%. 15,17,18 The DN4 score is a reliable, validated, quick, and sensitive tool for evaluating neuropathic pain. 37 However, the effect of neuropathic pain on acute pain and analgesic use after surgery has never before been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…e free nerve fibers, which are rich in the subacromial tissues (subacromial capsule, rotator cuff tendon, and biceps long head tendon), are activated in the case of inflammation or injury and thus led to shoulder pain [14]. In addition to nociceptive pain, studies have shown that 10.9% of patients with rotator cuff injury may also suffer from neuropathic pain [15]. Peripheral nerves, such as suprascapular nerve, can be injured by inflammation or stimulated by prostaglandin, substance P, and other chemicals released from damaged cells and inflammatory cells, leading to the sensitization of nociceptors which amplified its afferent nerve signals, and then resulted in peripheral sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with rotator cuff tears, in particular, exhibit neuropathic features [ 6 - 7 , 22 ]. Relevant reports for patients with NeuP in rotator cuff ruptures demonstrate percentages of 10.9 % [ 20 ] and 15.8% [ 6 ], respectively, but in our study, the proportion climbed to 18.8%.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to investigate the existence of NeuP in patients with a rotator cuff tear, as well as factors that may be prognostic of NeuP development. So far, investigations in patients with rotator cuff diseases have employed pain measurement tools like visual analog scale (VAS), as well as more NeuP specific ones like Douleur Neuropathique 4 Question (DN4) and Pain Detect [ 6 , 7 ]. To the best of our knowledge, no studies have investigated whether a questionnaire such as Shoulder Pain and Disability Index (SPADI) might be used as a prognostic factor for the development of NeuP in chronic shoulder pain.…”
Section: Introductionmentioning
confidence: 99%